Changes of intuition in paranoid personality disorder - Kerrin Artemis Jacobs; Kerrin Artemis Jacobs (Frontiers in Psychiatry, 2024)
Wherever psychopathology operates with the concept of (disorders of) the self and personality, it can address the role of the intuitive access we have toward ourselves, others, and the world. This study discusses the concept of oikeiôsis. It examines its role in explaining paranoia as a change in intuitive self-and-world relatedness. In the first step, symptomatic features of paranoid personality disorder are sketched, with a focus on the explanatory role of attentional and interpretative biases, which correlate with significant changes in intuitive processing. In the second step, the prototypical phenomenality of feelings of unfamiliarity and mistrust are discussed against the backdrop of changes of oikeiôsis in paranoid personality disorder. In the third step, the main therapeutic challenge in treating paranoid personality disorder—building a trustful relationship—is explored. It is concluded that the notion of oikeiôsis resonates particularly with introspection-based therapeutic approaches.